Probiotics as Means of Diseases Control in Aquaculture, a Review of Current Knowledge and Future Perspectives - Hoseinifar, Seyed Hossein; Sun, Yun-Zhang; Wang, Anran; Zhou, Zhigang (Frontiers in Microbiology, 2018)
Along with the intensification of culture systems to meet the increasing global demands, there was an elevated risk for diseases outbreak and substantial lose loss for farmers. In view of several drawbacks caused by prophylactic administration of antibiotics, strict regulations have been established to ban or minimize their application in aquaculture. As an alternative to antibiotics, dietary administration of feed additives has received increasing attention during the past three decades. Probiotics, prebiotics, synbiotics and medicinal plants were among the most promising feed supplements for control or treatments of bacterial, viral and parasitic diseases of fish and shellfish. The present review summarizes and discusses the topic of potential application of probiotics as a means of disease control with comprehensive look at the available literature. The possible mode of action of probiotics (Strengthening immune response, competition for binding sites, production of antibacterial substances, and competition for nutrients) in providing protection against diseases is described. Besides, we have classified different pathogens and separately described the effects of probiotics as protective strategy. Furthermore, we have addressed the gaps of existing knowledge as well as the topics that merit further investigations. Overall, the present review paper revealed potential of different probiont to be used as protective agent against various pathogens.